HUBUNGAN ANTARA TINGKAT PENGETAHUAN MASYARAKAT TENTANG PENYAKIT DBD DENGAN UPAYA PENCEGAHAN DBD DI DESA SUKOREJO MUSUK BOYOLALI - Austariyani, Nessma Putri; Widodo, Arif (Jurnal Berita Ilmu Keperawatan, 2011)
Dengue Hemorrhagic fever (DHF) is a desease happening in Indonesia. This desease can struck all of people especially children. From prevention, the important thing is to control Aedes aeygepti mosquito as the main cause it can be fought focus desease (FFD) phisicly and chemistryly. This fighting and preventing need a good knowledge on society in order to prevent desease well. This research is proposed to recognize the releation between the society knowledge about DHF desease with DHF prevention in Sukorejo, Musuk, Boyolali. The type of research is quantitative non experimental by using â€œCross Sectionalâ€. The sample of research are 89 persons that are the group of family from Tegalrejo village by using â€œTotal Samplingâ€ technique. Data collection in this research uses knowledge quesioner about DHF desease and check list sheet containing respondens prevention of DHF. This research is analyzed by using â€œChi Squareâ€ test. The result of the research shows that many respondens have a poor knowledge about DHF with total number 35 people (39,3%). The most respondens have a poor prevention effort about DHF desease with total number 41 people (46,1%). The result of the data hypothesis research shows that ï£ 2 = 17,88 with pvalue = 0,001. The conclusions is that there is a relation between the society knowledge level about DHF desease with prevention effort of DHF in Sukorejo, Musuk, Boyolali